Cover Feature: Model‐Free Estimation of Energy‐Transfer Timescales in a Closely Emitting CdSe/ZnS Quantum Dot and Rhodamine 6G FRET Couple (Chem. Asian J. 21/2018). Issue 21 (17th October 2018) - Bharadwaj, Kiran; Koley, Somnath; Jana, Subhra; Ghosh, Subhadip
Abstract : A state‐of‐the‐art analysis of FRET : Measurements of Förster resonance energy transfer (FRET) timescales are often complicated by close emission band positions of the donor and acceptor molecules, and by various other excited‐state processes. A mechanistic analysis of the time‐resolved emission spectra of a FRET pair allows the omission of other excited‐state processes from FRET. The model‐free approach of FRET analysis presented in this study, with quantum dot–dye as a FRET pair, indicates that FRET can even be a kinetic ruler, which provides a precise measurement of the timescale of the molecular fluctuations or structural rearrangements. The cover image illustrates how the proposed analysis method separates close emissions of the donor and acceptor, and the FRET kinetics when mixed with other processes. More information can be found in the Full Paper by Subhadip Ghosh et al. onpage 3296 in Issue 21, 2018 (DOI:10.1002/asia.201801272 ).